Damage suffered by Hanuman Dhoka after the 2015 Nepal Earthquakes - Xavier Romão (2015)
The current report presents findings by the ICCROM-ICOMOS-Smithsonian Institute team that visited some of the interior areas of Hanuman Dhoka after the April/May 2015 earthquakes on the 26th of May 2015. The purpose of the visit was to assess the stability conditions of the interior areas of Hanuman Dhoka in order to witness the overall damage of the movable heritage and to analyse the possibility of evacuating and rescuing it. The visit was requested by the Department of Archaeology of Nepal and the members of the ICCROM-ICOMOS-Smithsonian Institute team that visited the building were escorted by museum staff members. Given the high national significance of the Hanuman Dhoka palace and museum buildings, it is important that emergency stabilization of the heritage structures and collections is addressed in a holistic way. The aim of the first aid should be to assess and document damage using past documentation, prevent further damage and promote early recovery through prioritization of conservation treatments (of buildings and collections), and ensure business continuity through creative use/reuse while the stabilization and recovery work is underway.